Diagnostic reference level for computed tomography thorax examination: a single centre study / Muhammad Syafiq Shamsulnidza and Mohd Hafizi Mahmud - Shamsulnidza, Muhammad Syafiq; Mahmud, Mohd Hafizi (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
The increased number of CT Thorax examinations has shown an increase in frequency of patients exposed to medical radiation. Therefore, the recent radiation exposure from CT thorax should be revised to achieve dose optimization. This study aimed to determine a local diagnostic reference level (DRL) in CT thorax study. Data on CT thorax cases (n=307) were retrieved retrospectively from the Picture Archiving Communication System (PACS). Data input including CT scanner model, manufacturer and scanning parameters were incorporated in the CT-EXPO software. Weighted CT dose index (CTDIw), volume CT dose index (CTDIvol), dose length product (DLP) and effective dose (E) were automatically generated from the input. The data was presented as 75 th percentile and compared with the previous established national DRL report from the Ministry of Health Malaysia. The results demonstrated DRLs of CTDIw , CTDvol , E and DLP are significantly lower than the established national DRLs (p < 0.001 and p = 0.011, respectively) with reduction of 62.2%, 62.2%, 32.6% and 5.5%, respectively. The dose variations between local and national DRL may suggest for dose optimization in CT thorax examination.